Equal opportunity policy and feminist political science: The "invisible avant-garde" of governance research? - Silke Bothfeld; Mara Kuhl (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2007)
In Germany equal opportunity policy has been conducted from the beginning by forms of regulation, which are currently the subject of governance research. Feminist political science can thus offer important answers to the core questions of this new research perspective. By drawing on the main results of feminist research, the authors first clarify the boundaries of governance in the areas law, the economy, and social policy. Specifically, the diversity of forms and modes of governance will be illustrated for policies concerning wage equality, equality in childcare, and in administrative policy. In the conclusion the authors address the synergetic effects and the common concerns of feminist political science and governance research. – – In Deutschland wurde Gleichstellungspolitik von Beginn an über Steuerungsformen betrieben, die heute Gegenstand der Governanceforschung sind. Die feministische Politikwissenschaft kann darum dieser neuen Forschungsperspektive wichtige Antworten zu ihren Kernfragen anbieten. Im Rückgriff auf zentrale Ergebnisse feministischer Forschung machen die Autorinnen die Grenzen der Steuerbarkeit in den Bereichen Recht, Ökonomie und Sozialpolitik deutlich. Konkret wird die Vielfalt der Gover nanceformen und -modi an der Politik zu Entgeltgleichheit, zu Gleichheit in der Sorgearbeit und in der Verwaltungspolitik herausgearbeitet. Im Fazit werden die Synergieeffekte und die gemeinsamen Anliegen der feministischen Politikwissenschaft und der Governanceforschung aufgezeigt.
Keywords: 300